Pedestrians’ behavior towards the use of footbridges under the impact of motivational alerting posters: The case of Ipoh city, Malaysia - Hasan, R. (Aracne Ed, 2017)
This paper presents the results of a research project conducted in Ipoh city, Malaysia. It endeavors to rank the most affecting factors on using the footbridge from the pedestrians' perspective. The usage rate of four footbridges was observed, and thirteen factors that affect the usage of the footbridge were investigated by using the questionnaire. The relative importance index method was used to determine the ranking of these factors. An applicable enhancement scenario to improve the usage rate was designed and tested through a field experiment and its effect on the pedestrians' decisions when crossing the street was assessed. The difference between the before-treatment situation and the after-treatment situation of this scenario was determined and analyzed by using Z statistic test to compare two sample proportions. The existence of an escalator and the role of parents in educating their children about the safety awareness were ranked first of importance among the whole factors. Overall, the implementation of the site enhancement procedure showed that the installation of alerting posters had no effect on pedestrians' behavior to motivate them to utilize the footbridge more. Parents and schools are required to provide enough effort for enlightening the children about safety. The paper suggests a longitudinal study about testing the changes in the pedestrians' behavior over time through a successful motive. To improve the performance, escalators should be more taken into account in the construction of pedestrian bridges in order to save the time and to overtake the tiredness. These findings will provide information about enhancing the safety procedures for pedestrians when stakeholders decide to build new footbridges in specific locations. © 2017, Aracne Ed. All rights reserved.